Mental toughness training - Beattie, S.; Hardy, L.; Cooke, A.; Gucciardi, D. (Skill acquisition in sport: research, theory and practice, 2020)
To conclude, mental toughness cannot be developed in a void of adversity, The qualitative work showing that tough training environments and transformational delivery of punishment-driven interventions support this line of thinking. Furthermore, researchers have shown that self-regulated training environments (where the athlete takes ownership of their own training), partially explains the relationship between selfreport ratings of mental toughness and coach assessment of how well the athlete performs under pressure. Also, there is a need for mental toughness interventions to be more individualised. To fully understand the athlete and tailor individualised interventions, the three layers of understanding pertaining to mentaltoughness should prove helpful. Moreover, we need to better understand the relationships between self-report mental toughness assessments, its correlates, objectively assessed mentally tough behaviours, psychophysiological responses to stress, and performance related variables under pressure. For example, it is unlikely that all behaviours demonstrated by the athlete that promote performance under pressure could be termed mentally tough behaviours. Finally, we also recommend that future mental toughness interventions are based on principles of maximizing transparency and clarity in reporting and intervention development.